Ergonomic design of foot-operated resistance spot welding interface using multi-criteria decision-making approach. - Alam, Md Dilshad; Ali khan, Imtiaz (Work, 2025)
Background: Manual spot-welding operators often engage in repetitive motions, awkward postures, and prolonged standing. These factors increase the risk of work-related musculoskeletal disorders (WMSDs), particularly affecting the lower limbs and back. Additionally, inadequate workstation design impacts workers' health, safety, and productivity. Objective: Identify the optimal conditions for the spot-welding interface using a multi-criteria decision-making (MCDM) approach with three input parameters: pedal height (30, 35, 40 cm), worker distance (70, 80, 90 cm) and worksheet thickness (22, 25, 30 gauge). Methods: The study employed L27 orthogonal array experimental design. Entropy Weight Method (EWM) was used to determine weight of each factor. The optimal input parameters were identified using Weighted Aggregated Sum Product Assessment (WASPAS) method, with validation from Weighted Grey Relational Analysis (WGRA) and the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS). Analysis of Variance (ANOVA) determined the significance of input parameters, and a confirmation test validated the findings. Results: EWM calculated a weight of 0.3404 to task time, 0.3401 to pedal force, and 0.3193 to comfort level. WASPAS, WGRA, and TOPSIS identified the optimal parameters as pedal height of 35 cm, worker distance of 80 cm, and worksheet thickness of 30-gauge. ANOVA showed that worksheet thickness had the greatest impact on response, followed by worker distance and pedal height. The confirmation test validated the result with high reliability (0.88% error). Conclusion: This study explored ergonomic recommendations for optimizing spot-welding environments using a statistical and MCDM model focused on improving pedal force, task time, and comfort.